2013
DOI: 10.1371/journal.pone.0069043
|View full text |Cite|
|
Sign up to set email alerts
|

Long Term Suboxone™ Emotional Reactivity As Measured by Automatic Detection in Speech

Abstract: Addictions to illicit drugs are among the nation’s most critical public health and societal problems. The current opioid prescription epidemic and the need for buprenorphine/naloxone (Suboxone®; SUBX) as an opioid maintenance substance, and its growing street diversion provided impetus to determine affective states (“true ground emotionality”) in long-term SUBX patients. Toward the goal of effective monitoring, we utilized emotion-detection in speech as a measure of “true” emotionality in 36 SUBX patients comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…There are a number of reports of serious withdrawal symptoms in individuals using BUP [18,19]. additionally, long-term users of BUP (average 1.6 years) have difficulty experiencing pleasure and other emotions [20]. They discount happiness and tend to be unaware of the feeling of sadness and anxiety.…”
Section: Do We Really Need To Continue Pharmacotherapy For Opioid Usementioning
confidence: 99%
“…There are a number of reports of serious withdrawal symptoms in individuals using BUP [18,19]. additionally, long-term users of BUP (average 1.6 years) have difficulty experiencing pleasure and other emotions [20]. They discount happiness and tend to be unaware of the feeling of sadness and anxiety.…”
Section: Do We Really Need To Continue Pharmacotherapy For Opioid Usementioning
confidence: 99%
“…Bup/nal in a number and variety of forms (e.g., Suboxone R and Zubsolve R ) and methadone, are the available FDA approved MAT for opioid maintenance therapy. The success of the acute use of bup/nal during treatment is qualified by the potential for addiction liability, and the antireward effects of long-term use (Elman, Borsook, & Volkow, 2013;Hill et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Outcome studies that include other cofactors such as the length of stay, and experiments that use other tools to access, for example, emotionality measures (Hill et al, 2013) and fMRI to investigate the neural mechanisms that elicit reward-seeking and relapse in addictive behaviors (Volkow, Fowler, Wang, Telang, & Baler, 2009) are encouraged. To further enlighten our understanding of the psychological status of recovering patients, larger studies are required.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rationale of such a blockade always remains questionable, as it strengthens the hypodopaminergic state of the brain reward circuits, and thus sustains the craving rather than helping the person achieve relief. Moreover, a recent study observed emotional impairment utilizing a sophisticated voice recognition method in long-term (average 1.6 years) patients on Suboxone maintenance therapy (Hill et al 2013). From this perspective, the importance of utilizing dopamine agonist therapy to treat addictive disorders instead of blocking natural dopaminergic activity seems more prudent in the long term (Blum et al, 2014a).…”
Section: Dopamine Agonist Therapy: Reasons For Blocking Rewardmentioning
confidence: 99%